AS COTAS RACIAIS NA UNIVERSIDADE FEDERAL DO MARANHÃO: a trajetória do estranho - CAMARGO, Amilton Carlos (2016)
Affirmative action, via reservation quotas, has allowed the entry of blacks quota students in Universidade Federal do Maranhão since 2007. So there have been changes in the campus Bacanga from the entry of these black students, but little has been researched in this regard, and the produced research highlights are commonly perceptions of teachers, leaders and institutional leaders. Intended, originally, to give voice to these shareholders black, showing your activity on campus. This survey of the empirical experience of the author as an institutional teaching, makes use of spontaneous comments of undergraduates, graduate, teachers, coordenators and other employees of UFMA. The focus is on the trajectory of 9 shareholders black students who were interviewed, 7 of them organized in a group calling itself, G7. From the strange notion, we seek to understand the representations of these witnesses, anchored in Bourdieu. It is understood that the quota students experience difficulties of acceptance and educational attainment in this space, and seek, on their own and through assimilation, play the principle of personal merit. They realize that the bondholder label them inferior before the academic community.